2016
DOI: 10.1111/aas.12681
|View full text |Cite
|
Sign up to set email alerts
|

Persistent postsurgical pain after video‐assisted thoracic surgery – an observational study

Abstract: The incidence of PPP, nerve damage (based on QST) and pain-related functional impairment following VATS was lower than reported following thoracotomy. No psychological or other factors predicted PPP. These findings call for further large-scale studies to support VATS to decrease PPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
43
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 26 publications
8
43
1
Order By: Relevance
“…Measuring psychosocial factors before surgery enabled us to test this hypothesis in our study. Contrary to our expectations, and consistent with a recent observational study on VATS patients, 6 none of the pre-operative psychosocial variables were significantly associated with the presence of chronic pain. Our negative results may be due to the small sample size in our study and the large number of associations tested.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Measuring psychosocial factors before surgery enabled us to test this hypothesis in our study. Contrary to our expectations, and consistent with a recent observational study on VATS patients, 6 none of the pre-operative psychosocial variables were significantly associated with the presence of chronic pain. Our negative results may be due to the small sample size in our study and the large number of associations tested.…”
Section: Discussionsupporting
confidence: 77%
“…5 A few studies evaluated results for chronic pain after video-assisted thoracic surgery (VATS, thoracoscopy); 5,6 however, the data were not sufficient to summarize.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive and psychological factors have been reported to have important roles in the severity of postoperative pain (9,20,21,24). High levels of pain catastrophizing are associated with heightened pain experience and appear to contribute to the development of chronic pain (24).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of pain catastrophizing are associated with heightened pain experience and appear to contribute to the development of chronic pain (24). However, Wildgaard and colleagues (9) reported that although pain-related functional impairment after VATS was lower, no psychological factors could be used to predict persistent postoperative pain. In addition, Khan and workers (24) reviewed pain catastrophizing and its association with postoperative pain and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative pain after thoracic surgery deserves greater attention. If not solely because of a desire to relieve discomfort in the period following surgery, then in an effort to minimize the risk of development of chronic pain in the months and years The few studies that have been published (4,12,13), supports the findings of Bayman et al but larger studies are warranted to reach a final conclusion. A more aggressive approach to pain management and multimodal analgesia is warranted and further studies are still needed.…”
mentioning
confidence: 79%